Perovskite-based photocatalysts for organic contaminants removal: Current status and future perspectives - Kong, Jiejing; Yang, Ting; Rui, Zebao; Ji, Hongbing (Catalysis today, 2019)
[Display omitted] •Perovskite-related photocatalysts for organic contaminants removal are reviewed.•Design strategies of perovskite-related photocatalysts are highlighted.•Future perspectives of perovskite-related photocatalysts are proposed. The development of new generation photocatalytic materials for the organic contaminants removal has been a research focus. Perovskite and perovskite-related structures offer a broad scope in designing novel photocatalysts for this process. The present review summarizes and highlights the state-of-the-art progress of third-generation photocatalysts perovskite and perovskite-related semiconductors, and their application for the photocatalytic decomposition of both waterborne and airborne organic contaminants. Special attention is paid to the design strategies for promoting the photocatalytic performance of perovskite and perovskite-related materials, including ion doping/substitution, noble metal decoration, heterojunctions formation and morphology regulation. Future perspectives of perovskite-related photocatalysts are also included in this review.